2019
DOI: 10.1101/843037
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hippocampal spatial memory representations in mice are heterogeneously stable

Abstract: The population of hippocampal neurons actively coding space continually changes across days as mice repeatedly perform tasks. Many hippocampal place cells become inactive while other previously silent neurons become active, challenging the belief that stable behaviors and memory representations are supported by stable patterns of neural activity. Active cell replacement may disambiguate unique episodes that contain overlapping memory cues, and could contribute to reorganization of memory representations. How a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…In our recent work ( Driscoll et al, 2017 ), we found that neural activity–behavior relationships in individual posterior parietal cortex (PPC) neurons continually changed over many days during a repeated virtual navigation task. Similar ‘representational drift’ has been shown in other neocortical areas and hippocampus ( Attardo et al, 2015 ; Ziv et al, 2013 ; Levy et al, 2019 ). Importantly, these studies showed that representational drift is observed in brain areas essential for performing the task long after the task has been learned.…”
Section: Introductionsupporting
confidence: 73%
“…In our recent work ( Driscoll et al, 2017 ), we found that neural activity–behavior relationships in individual posterior parietal cortex (PPC) neurons continually changed over many days during a repeated virtual navigation task. Similar ‘representational drift’ has been shown in other neocortical areas and hippocampus ( Attardo et al, 2015 ; Ziv et al, 2013 ; Levy et al, 2019 ). Importantly, these studies showed that representational drift is observed in brain areas essential for performing the task long after the task has been learned.…”
Section: Introductionsupporting
confidence: 73%
“…To distinguish consistent sequences from stochastic dynamics (Figure 1), we examined the consistency of the neuronal dynamics across two timescales while mice performed reward-based navigational tasks (Mau et al, 2018;Levy, Kinsky, Mau, Sullivan, & Hasselmo, 2019;Rubin et al, 2015). In all experiments, each session consists of multiple trials, during which mice were trained to navigate through an environment to obtain rewards (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…First, it suggests that variations in the firing of grid and place cells on di↵erent visits to a location might be due not only to variable paths taken within a single map [75] but to the retrieval of entirely di↵erent maps. Second, these multiple, stochastically generated maps might subsequently be easy to harness for contextual di↵erentiation, for instance like "splitter" cells [58,[76][77][78].…”
Section: Experimental Predictionsmentioning
confidence: 99%